Legal Protection for Consumers Due to Negligence in the Process of Funds Transfered by BRI - Edi Wahjuni; Ayu Citra Santyaningtyas; Abdul Hady Dawud (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article examines legal protection for consumers due to negligence in the process of funds transfer by BRI. The method used is the normative legal research. This study uses statue and conceptual approach. The legal materials used in this study are primary legal and secondary legal sources. The results obtained from the research. Form of protection law against consumers namely external protection. In this case the basis of consumer protection is listed in Law Number 8 of 1999, Law No.10 of 1998, Law Number 21 of 2011. Consumers who are harmed can claim legal responsibility to the business actors). This negligence case has also violated Law Number 10 of 1998 stating bank employees should apply the prudential banking principle.